Identifying factors that underpin student decisions to pursue the Doctor of Pharmacy degree at Atlantic Canadian Universities: Protocol for a mixed methods study. - Tiffany A Lee; Amit Sundly; Stephen D Coombs; Gerald J Galway (PLoS ONE)
Several international studies have investigated academic decision-making in higher education, but there is limited research on students' choice to study pharmacy in the Canadian context. While there is some variation across jurisdictions, decisions to enroll in a particular degree program fall into several decision-making domains (e.g., personal, family, institutional, social, and economic). These findings have been theorized in various ways, for example, through social cognitive theory and social reproduction theory. The purpose of this study is to gain a better understanding of the personal, family, institutional, social, and economic factors that underpin student decisions to pursue the Doctor of Pharmacy (PharmD) degree at Atlantic Canadian Universities and to explore barriers to pursuing a pharmacy degree. The proposed study uses an explanatory sequential mixed-methods design consisting of a quantitative survey followed by qualitative interviews. All entry-to-practice PharmD students and graduates in Atlantic Canada are eligible to participate. The survey consists of several Likert scale questions associated with five decision-making domains, as well as several socio-demographic questions. Descriptive statistics and frequency counts will be used to describe the data; differences across decision-making domains, by gender and other demographic groupings, will be analyzed using inferential statistics. Semi-structured interviews with a sample of 12 to 15 participants will be conducted to further understand and explain the quantitative results. We will engage in thematic analysis of qualitative data. The findings of this research will provide insight into the decision-making patterns and socio-demographic characteristics of students who have chosen to pursue a PharmD. Important information will be gathered to inform health professional education and workforce planning, which we believe will contribute to improving healthcare resource capacity and patient outcomes in Atlantic Canada. The results of this project will also inform future recruitment strategies and admission criteria and support educators in the secondary school system in providing evidence-informed career counselling advice for students interested in pursuing a degree in pharmacy. The findings of this study may also be useful to educational leaders and policymakers.